2018
DOI: 10.1155/2018/5681652
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Difficulty Adjustment (DDA) in Computer Games: A Review

Abstract: Dynamic difficulty adjustment (DDA) is a method of automatically modifying a game’s features, behaviors, and scenarios in real-time, depending on the player’s skill, so that the player, when the game is very simple, does not feel bored or frustrated, when it is very difficult. The intent of the DDA is to keep the player engrossed till the end and to provide him/her with a challenging experience. In traditional games, difficulty levels increase linearly or stepwise during the course of the game. The features su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(69 citation statements)
references
References 26 publications
(32 reference statements)
0
47
0
2
Order By: Relevance
“…Several researchers claim that early interventions should also try to reduce distress at failure, and preserve confidence in ability to solve math problems (Dowker, Cheriton, Horton, & Mark, 2019). Adaptive games might reduce frustrations, hence possibly reducing anxiety as children experience more success and less failure due to the integrated adaptivity (Hubalovsky et al , 2019; Jansen et al , 2013; Zohaib, 2018). Only a limited number of intervention studies investigated this assumption.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Several researchers claim that early interventions should also try to reduce distress at failure, and preserve confidence in ability to solve math problems (Dowker, Cheriton, Horton, & Mark, 2019). Adaptive games might reduce frustrations, hence possibly reducing anxiety as children experience more success and less failure due to the integrated adaptivity (Hubalovsky et al , 2019; Jansen et al , 2013; Zohaib, 2018). Only a limited number of intervention studies investigated this assumption.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The goal of the "Monopolist" player was to keep the player in the Csikszentmihalyi 's "Flow zone" [16], where the player's skills correlate with the difficulty of the challenge. The player should be as difficult to play with as possible, but keeping the human player away from the too-difficult or too-easy zone, thus ensuring that his/her entertainment is at optimal level.…”
Section: The "Monopolist" Playermentioning
confidence: 99%
“…The use of Dynamic Difficulty Adjustment techniques allows us to match player ability and the challenge difficulty in real time, while he/she is playing, therefore maximizing the reward and acquisition of knowledge, skill or competence [16].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, dynamic difficulty adjustment or dynamic difficulty balancing changes the game behavior according to the skill level of the players. For this purpose, the dynamic difficulty adjustment requires evaluation of the player's performance (through game scores, time, number of errors, player's decisions, etc) and adjustment of a set of game variables that regulate difficulty [ 10 ]. It has been shown that a dynamic approach that uses gamer behavior data presents better learning outcomes than an incremental difficulty approach [ 7 ].…”
Section: Introductionmentioning
confidence: 99%